재가장기요양서비스 이용 노인의 삶의 의미 영향요인 - 김은지 (The Graduate School, Ajou University, 2024)
본 연구는 재가장기요양서비스 이용 노인의 일상생활 수행능력, 우울, 사회적 지지와 삶의 의미 수준을 확인하고, 삶의 의미에 영향을 미치는 영향요인을 파악하고자 하는 서술적 상관관계 조사연구이다. 본 연구는 경기도 2개시(안산시, 수원시) 소재 7개 주간보호센터 이용 노인 121명을 대상으로 하였으며, 2023년 9월 28일부터 10월 15일까지 자가보고식 설문 조사를 통해 자료수집 하였다._x000D_ 연구도구로써, 일상생활 수행능력은 Katz 등(1963)이 개발한 Index of Activities of Daily Living (ADL) 도구를 원장원 등(2002)이 한국어로 번안한 한국형 일상생활 활동 측정도구(K-ADL)로 측정하였고, 우울은 Yesavage와 Sheikh (1986)가 개발한 Geriatric Depression Scale Short Form (GDSSF)을 기백석(1996)이 한국인에 맞게 표준화한 한국판 노인 우울 척도 단축형(GDSSF-K)을 사용하여 측정하였다. 사회적 지지는 Zimet, Dahlemm, Zimet과 Farley (1988)가 개발하고 신준섭과 이영분(1999)이 번안한 Multidimensional Scale of Perceived Social Support (MSPSS)를 이용하여 측정하였고, 삶의 의미는 Steger, Frazier, Oishi와 Kaler (2004)가 개발한 삶의 의미 척도(Meaning in Life Questionnaire; MLQ)를 원두리, 김교헌 권선중(2005)이 한국어로 번안한 척도를 사용하였다. 수집된 자료는 SPSS 29.0 프로그램을 사용하여 기술통계, 독립표본 t-검정, ANOVA(사후분석 Scheffé test), Pearson의 상관계수, 위계적 다중회귀분석을 이용하여 분석하였다._x000D_ _x000D_ 본 연구의 주요 결과는 다음과 같다. _x000D_ _x000D_ 1. 대상자의 삶의 의미는 70점 만점에 평균 42.95±14.27점이었으며, 일상생활 수행능력은 21점 만점에 평균 8.21±1.91점, 우울은 15점 만점에 평균 5.54±4.52, 사회적 지지는 60점 만점에 평균 40.38±10.42점으로 나타났다._x000D_ 2. 대상자의 인구사회학적 특성에 따른 삶의 의미 점수의 차이를 파악한 결과, 연령(t=2.38, p=.019)과 학력(F=3.773, p=.026)에 따라 삶의 의미에 유의한 차이를 보였다._x000D_ 3. 대상자의 삶의 의미는 일상생활 수행능력(r=-.20, p=.026) 및 우울(r=-.31, p<.001)과 통계적으로 유의한 음의 상관관계가 있는 것으로 나타났고, 사회적 지지와는 통계적으로 유의한 양의 상관관계가 있는 것으로 나타났다(r=.51, p<.001)._x000D_ 4. 대상자의 삶의 의미 영향요인을 파악하기 위해 위계적 다중회귀분석을 실시한 결과, 먼저 인구사회학적 특성 중 단변량 분석에서 유의성을 나타낸 변수인 연령과 학력들을 투입하였을 때 설명력은 7%(R²=.070, adjusted R²=.047)였고(F=2.96, p=.035), 다음으로 본 연구의 주요 변수인 일상생활 수행능력, 우울, 사회적 지지를 추가로 투입하였을 때 설명력은 26.7%(△R²=.267) 증가된 33.7%(R²=.337, adjusted R²=.302)로 나타났다(F=15.25, p<.001). 대상자의 삶의 의미에 대한 유의한 개별 영향요인은 사회적 지지(β =.45, p<.001)와 우울(β =-.16, p=.048) 순으로 나타났다. 즉, 재가장기요양서비스 이용 노인의 사회적 지지가 높을수록, 우울은 낮을수록, 삶의 의미가 높은 것으로 나타났다. _x000D_ _x000D_ 본 연구 결과, 재가장기요양서비스 이용 노인의 삶의 의미는 중등도 수준이었으며, 사회적 지지가 높을수록, 우울은 낮을수록 삶의 의미가 높아짐을 확인할 수 있었다. 이에, 노인의 사회적 지지를 높이고, 우울을 낮출 수 있도록 다양하고 전문적인 프로그램들을 개발 및 활용함으로써, 재가장기요양서비스 이용 노인의 삶의 의미 향상을 기대할 수 있을 것으로 사료된다.|This descriptive correlational research aims to examine the levels of activities of daily living (ADL), depression, social support, and meaning in life and identify the influencing factors on the meaning in life of older adults utilizing in-home services under the long-term care insurance system. _x000D_ We collected 121 older adults from 7 day-care centers in two cities in Gyeonggi province, South Korea. Data were collected through self-reported questionnaires from September to October 2023. The Korean ADL (K-ADL) developed by Katz et al. (1963) and translated by Won (2002) employed to measure ADL, the Korean Geriatric Depression Scale Short Form developed by Yesavage & Sheikh (1986) and translated by Gi (1996) used for measuring depression, the Korean version of the Multidimensional Scale of Perceived Social Support developed by Zimet et al. (1988) and translated by Shin & Lee (1999) employed to measure social support, and the Korean version of Meaning in Life Questionnaire developed by Steger et al. (2006) and translated by Won et al. (2005) used for measuring meaning in life of the participants. Data analyses were conducted using the SPSS 29.0 program, employing descriptive statistics, independent t-tests, ANOVA (followed by Scheffé test), Pearson's correlation coefficient, and hierarchical multiple regression analysis. _x000D_ _x000D_ The following are the main findings of this study:_x000D_ _x000D_ 1. The mean age of the participants was 82.85 years, and 96 (79.3%) were women. Participants’ mean scores of ADL, depression, social support, and meaning in life were 8.21±1.91 (out of 21), 5.54±4.52 (out of 15), 40.38±10.42 (out of 60), and 42.95±14.27 (out of 70), respectively._x000D_ _x000D_ 2. There were statistically significant differences in the meaning in life among the participants according to age (t=2.38, p=.019) and educational level (F=3.773, p=.026)._x000D_ _x000D_ 3. Participants’ meaning in life was negatively correlated with ADL (r=-.20, p=.026) and depression (r=-.31, p<.001) and positively correlated with social support (r=.51, p<.001)._x000D_ _x000D_ 4. As a result of the hierarchical regression analysis, factors influencing the meaning in life of the participants were found to be social support (β=.45, p<.001) and depression (β=-.16, p=.048). The explanatory power of the final model was 33.7% (F=15.25, p<.001). _x000D_ _x000D_ Based on the results of this study, efforts to enhance social support and reduce depressive symptoms are recommended to improve the meaning in life of older adults utilizing in-home services under the long-term care insurance system. Specifically, it is necessary to closely identify older adults’ depressive symptoms and further strengthen social support, including policy support and support from healthcare professionals in the facilities, in order to ultimately improve those populations’ meaning in life.
학위논문(석사)--간호학과,2024. 2
Keywords: 노인; 사회적 지지; 삶의 의미; 우울; 재가장기요양서비스